TINJAUAN IMPLEMENTASI DISPENSASI PERKAWINAN - Buwana, Sudibyo Aji Narendra; Damanik, Nadya; Habib, Muhammad (LPPM STIH Awang Long, 2025)
Marriage is the literal nature of living beings, especially humans. When the prospective husband or prospective wife is not yet 19 years old, either one or both of them, a marriage dispensation must be requested to the local religious court. The type of research used by researchers in this study is normative juridical. In this study, data processing and analysis used qualitative descriptive analysis. The conclusion is drawn deductively. The result of the research as a conclusion is the implementation of the implementation of marriage dispensation in Decision Number 3/Pdt.P/2024/PA.Kab.Mlg reviewed based on Law No. 16 Th. 2019 is in accordance with Article 7 paragraphs 1 and 2 of Law No. 16 th. 2019 which reads “marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years and reads ‘In the event of a deviation from the age provisions as referred to in paragraph (1), the parents of the male party and/or the parents of the female party may request dispensation to the Court on very urgent grounds accompanied by sufficient supporting evidence. The suggestions given by the researchers are that parents should always supervise and provide education to their respective children who are entering puberty so that they do not fall into promiscuity so that children avoid underage marriage so that parents do not apply for marriage dispensation, the Religious Court and the Regional Government of Malang Regency are expected to increase counseling efforts related to the impact that will arise as a result of the implementation of underage marriage and the judges who hear applications for marriage dispensation to be more thorough and careful, so that this application for marriage dispensation is treated as an emergency, so that it cannot be decided arbitrarily.